2005
DOI: 10.1016/s1472-6483(10)61145-5
|View full text |Cite
|
Sign up to set email alerts
|

PGD patients' and providers' attitudes to the use and regulation of preimplantation genetic diagnosis

Abstract: Preimplantation genetic diagnosis (PGD) providers and patients have a vested interest in policy related to the use and regulation of PGD. To understand their experiences and attitudes, 32 in-depth interviews were conducted. Participants included 13 people at risk of transmitting a single-gene alteration to their children (10/13 had actually used PGD to try to have an unaffected child) and 19 PGD service providers (four nurses, five genetic counsellors, two reproductive endocrinologists, two geneticists, two ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 47 publications
2
100
0
10
Order By: Relevance
“…A survey conducted by the HFEA found that, of those that agreed with PGD, the reasons for doing so were because it prevented further suffering within families where the condition is present and was a preferable technology to prenatal diagnosis [3]. Studies of the US general public, including PGD users, stress the importance of individual decision making regarding reproductive genetic technologies [19,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted by the HFEA found that, of those that agreed with PGD, the reasons for doing so were because it prevented further suffering within families where the condition is present and was a preferable technology to prenatal diagnosis [3]. Studies of the US general public, including PGD users, stress the importance of individual decision making regarding reproductive genetic technologies [19,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The focus group and interview responses provide a detailed and textured portrait of peoples' attitudes (31)(32)(33).…”
Section: Policy Issues and Public Attitudesmentioning
confidence: 99%
“…In another case, after being told that both embryos transferred into her uterus were unaffected females, a patient underwent ultrasound and follow-up prenatal testing. She learned she was pregnant with an affected male (10).…”
Section: Misdiagnosismentioning
confidence: 99%
“…In a series of interviews with patients undergoing PGD conducted by the Genetics and Public Policy Center, several women who became pregnant after single gene PGD reported having a misdiagnosis (10). One was told that the transferred embryos were carriers of the disease, but she subsequently learned during pregnancy from chorionic villus sampling (CVS) that the fetus was not a carrier.…”
Section: Misdiagnosismentioning
confidence: 99%